Effect of beta-lactoglobulin polymorphism and seasonality on bovine milk composition - Botaro, Bruno G.; Lima, Ygor V. R.; Aquino, Adriana A.; Fernandes, Raquel H. R.; Garcia, José Fernando [UNESP]; Santos, Marcos V. (Cambridge University Press, 2008)
The objective was to evaluate the effect of beta-lactoglobulin (beta-lg) polymorphism and seasonality on milk composition (fat, lactose, total solids, milk urea nitrogen, total protein, true protein, casein and somatic cell counts) of Holstein and Girolando cows. Milk and blood samples from 278 Holsteins cows and 156 Girolando cows were taken during two dry seasons and two rainy seasons, for milk composition analysis and to determine beta-lg genotypes, respectively. BB genotype was the most frequent for both breeds, followed by AA genotype for Holstein (BB>AA>AB) and by AB for Girolando cows (BB>AB>AA). No differences were found in milk compositional characteristics among genetic variants of beta-lg (AA, AB and BB) either between Holstein or Girolando cows. No association between milk composition and beta-lg genetic polymorphism was observed. During the dry season, independently of the breed considered, higher contents of lactose, true protein, casein and casein :true protein ratio were found.
Keywords: milk protein; beta-lactoglobulin; genetic variants; seasonality